Prove: (1 + csc x)/sec x - cot x = cos x
- print Print
- list Cite
Expert Answers
Tushar Chandra
| Certified Educator
calendarEducator since 2010
write12,554 answers
starTop subjects are Math, Science, and Business
The identity `(1 + csc x)/sec x - cot x = cos x` has to be proved.
`(1 + csc x)/sec x - cot x`
=> `(1 + 1/sin x)/(1/cos x) - (cos x)/(sin x)`
=> `(cos x + cos x/sin x) - (cos x)/(sin x)`
=> `cos x + cos x/sin x - (cos x)/(sin x)`
=> `cos x`
This proves that `(1 + csc x)/sec x - cot x = cos x`
Related Questions
- Prove the identity: csc x - cot x = sinx/1+cosx
- 1 Educator Answer
- Prove that (cot x)' = - csc^2 x
- 1 Educator Answer
- Prove csc^2 x + sec^2 x = csc^2 x sec^2 xRS shows the 2 sets being multiplied.
- 1 Educator Answer
- Prove that (cot x + tan x)(1/sec x + 1/cosec x)= cosec x + sec x.
- 1 Educator Answer
- Cot^2(x)/csc(x)-1=csc(x)+sen^2(x)+cos^2(x)
- 1 Educator Answer